2015
DOI: 10.3390/toxins7020439
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics of the Bio-Degradation Process of Aflatoxin B1 by Actinomycetes at an Initial pH of 6.0

Abstract: Contamination of food and feed by Aflatoxin B1 (AFB1) is a cause of serious economic and health problems. Different processes have been used to degrade AFB1. In this study, biological degradation of AFB1 was carried out using three Actinomycete species, Rhodococcus erythropolis ATCC 4277, Streptomyces lividans TK 24, and S. aureofaciens ATCC 10762, in liquid cultures. Biodegradation of AFB1 was optimised under a range of temperatures from 25 to 40 °C and pH values of 4.0 to 8.0. An initial concentration of 20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
54
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(59 citation statements)
references
References 32 publications
4
54
0
1
Order By: Relevance
“…2). Comparable results previously obtained in other similar studies also suggest that such degradation is a constitutive activity of the tested bacteria (Eshelli et al, 2015;Farzaneh et al, 2012;Guan et al, 2008;Samuel et al, 2014;Teniola et al, 2005).…”
Section: Afb 1 Degradation By Liquid Cultures and Lysatessupporting
confidence: 88%
See 2 more Smart Citations
“…2). Comparable results previously obtained in other similar studies also suggest that such degradation is a constitutive activity of the tested bacteria (Eshelli et al, 2015;Farzaneh et al, 2012;Guan et al, 2008;Samuel et al, 2014;Teniola et al, 2005).…”
Section: Afb 1 Degradation By Liquid Cultures and Lysatessupporting
confidence: 88%
“…Microsoft Excel, 2013 (Microsoft Corp., USA) was used to plot various graphs. A multivariate analysis, principal component analysis (PCA) was performed using JMP 12.1.0 statistical software (SAS Institute, Cary, North Carolina) to further summarize and describe the variations in the descriptive experimental factors (Eshelli et al, 2015). The results represent the average of triplicate determinations and are expressed as mean ± standard error of mean (SEM).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several Actinomycetes strains were revealed to be able to degrade directly mycotoxins. AFB1 (Cserh ati , 2013;Eshelli et al, 2015;Krifaton et al, 2011) andZON (Cserh ati et al, 2013;Krifaton et al, 2013) were reported to be degraded effectively by Streptomyces and Rhodococcus strains also. In the present study, elimination of genotoxicity was detected in the case of AFB1 by SOS Chromotest and in the case of ZON estrogenic effect was measured by BLYES.…”
Section: Discussionmentioning
confidence: 99%
“…Pseudomonas aeruginosa is another good degrader, providing 90 % reduction, however, its high optimal growth temperature (55°C) may be economically problematic [17]. Eshelli et al [22] investigated degradation products of AFB 1 and reported a degradation product with 236 amu molecular mass, which lacks the mutagenic lactone ring property and later this product participated in the citrate cycle.…”
Section: Introductionmentioning
confidence: 99%